دور الاتصال الرقمي في زيادة مرئية المؤسسات الجامعية - بن مسعود خديجة; بن قطش ايمان; د/ عطا الله طريف (جامعة عمار ثليجي الاغواط, 2024)
ملخص الدراسة: هدفت دراستنا الحالية لمعرفة دور الاتصال الرقمي في زيادة مرئية المؤسسات الجامعية وهذا من منظور عينة من أساتذة كلية العلوم الانسانية والعلوم الاسلامية والحضارة بجامعة عمار ثليجي بالأغواط، كما أن الدراسة تهدف أيضا إلى دراسة وسائل الاتصال الرقمي المستخدمة في جامعة الأغواط، واهم خصائص ووظائف الاتصال الرقمي كنوع اتصالي معتمد.. تم تطبيق أداة الدراسة المتمثلة في الاستبيان على عينة متكونة من 100أستاذ وأستاذة، وتم استخدام المنهج الوصفي التحليلي. وبعد جمع بيانات الدراسة تم تحليل هذه النتائج التي نلخصها فيما يلي:  أن استخدام الاتصال الرقمي في جامعة الأغواط له تأثيرات إيجابية كبيرة على التواصل والتفاعل داخل الجامعة، ويعزز من سمعتها وصورتها العامة.  أظهرت النتائج تفضيلًا كبيرًا للوسائل الرقمية مثل المواقع الإلكترونية ووسائل التواصل الاجتماعي، حيث ساهمت هذه الوسائل في تحسين فهم خدمات الجامعة وتسريع عملية التواصل وتعزيز المشاركة في الفعاليات الجامعية.  الاستخدام الفعّال للاتصال الرقمي يعزز الثقة بين الجامعة ومكوناتها ويساعد في جذب الكوادر الأكاديمية المتميزة وإبراز إنجازاتهم.  تواجه الجامعة تحديات في تطبيق استراتيجيات الاتصال الرقمي، أبرزها نقص الموارد المالية، وقلة الوعي بأهمية الاتصال الرقمي بين الكوادر الإدارية والأكاديمية، وغياب استراتيجيات واضحة للتواصل الرقمي.  يشكل ضعف تدفق البيانات ونقص التدريب والتطوير في مجال تكنولوجيا المعلومات تحديات إضافية تعيق فعالية الاتصال الرقمي. وتم تفسير النتائج وفق نتائج الدراسات السابقة، والتراث النظري المعتمد في فصول البحث الأولى. الكلمات المفتاحية: الاتصال الرقمي، مؤسسات التعليم العالي، المرئية. Abstract: Our current study aimed to understand the role of digital communication in increasing the visibility of university institutions from the perspective of a sample of professors from the Faculty of Humanities, Islamic Sciences, and Civilization at AmmarThliji University of Laghouat. The study also aimed to examine the digital communication tools used at Laghouat University and the main characteristics and functions of digital communication as a recognized communication type. A questionnaire was applied to a sample of 100 professors, and the descriptive-analytical method was used. After collecting the study data, the results were analyzed, and we summarize them as follows: The use of digital communication at Laghouat University has significant positive impacts on communication and interaction within the university, enhancing its reputation and public image. The results showed a strong preference for digital tools such as websites and social media, which have contributed to better understanding of the university's services, accelerating communication processes, and enhancing participation in university events. Effective use of digital communication boosts confidence between the university and its components, helps attract outstanding academic staff, and highlights their achievements. The university faces challenges in implementing digital communication strategies, the most prominent of which are a lack of financial resources, limited awareness of the importance of digital communication among administrative and academic staff, and the absence of clear digital communication strategies. Additional challenges hindering the effectiveness of digital communication include weak data flow and a lack of training and development in information technology. The results were interpreted according to previous studies and the theoretical framework established in the initial chapters of the research. Keywords: digital communication, higher education institutions, visibility.
دراسة ميدانية على عينة من اساتذة كلية العلوم الانسانية و الاسلامية و لاحضارة بجامعة الاغواط